Bolivia : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report, 2007)
The Report on the Observance of Standards and Codes (ROSC) Data Module provides an assessment of Bolivia's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS). The report reveals that the quality of Bolivia's macroeconomic statistics has improved over recent years. The statistics have been broadly adequate for macroeconomic analysis and policy design and monitoring. The authorities have demonstrated a commitment to pursue plans and programs to further improve their statistics.